High resolution SPM imaging of organic molecules with functionalized tips. (25th July 2017) - Jelínek, Pavel
Abstract: One of the most remarkable and exciting achievements in the field of scanning probe microscopy (SPM) in the last years is the unprecedented sub-molecular resolution of both atomic and electronic structures of single molecules deposited on solid state surfaces. Despite its youth, the technique has already brought many new possibilities to perform different kinds of measurements, which cannot be accomplished by other techniques. This opens new perspectives in advanced characterization of physical and chemical processes and properties of molecular structures on surfaces. Here, we discuss the history and recent progress of the high resolution imaging with a functionalized probe by means of atomic force microscopy (AFM), scanning tunnelling microscopy (STM) and inelastic electron tunneling spectroscopy (IETS). We describe the mechanisms responsible for the high-resolution AFM, STM and IETS–STM contrast. The complexity of this technique requires new theoretical approaches, where a relaxation of the functionalized probe is considered. We emphasise the similarities of the mechanism driving high-resolution SPM with other imaging methods. We also summarise briefly significant achievements and progress in different branches. Finally we provide brief perspectives and remaining challenges of the further refinement of these high-resolution methods.